COVID-19-Related Intestinal Ischemia in A 7-Year Old Boy - Balázs Fadgyas; Gábor István Garai; János Schnur; Viktória Irén Kiss; Viktória Vass; Enikő Mátyus; György Balázs; Tamas Cserni (Georg Thieme Verlag KG, 2022)
Severe abdominal pain and vomiting are common symptoms in children with pediatric multisystem inflammatory syndrome (PIMS). Mesenteric lymphadenitis and aseptic peritonitis are predominantly reported in cases where acute surgical abdomen was suspected and laparotomy was performed at the early stage of the pandemic. These reports generally discouraged surgeons to perform exploration in COVID-19-related cases and medical management was prioritized. Only a few COVID-19-specific surgical cases with intestinal ischemia were published. Here, we report another case of COVID-19-related intestinal ischemia complicated with Meckel's diverticulitis in a non-immunocompromised child who clearly required surgical intervention. In our case, the combination of COVID-19-related vasculitis and low blood pressure episodes may have contributed to this severe outcome.